2011
DOI: 10.1590/s1676-24442011000500004
|View full text |Cite
|
Sign up to set email alerts
|

Stenotrophomonas maltophilia: resistência emergente ao SMX-TMP em isolados brasileiros. uma realidade?

Abstract: Introdução: Stenotrophomonas maltophilia é um importante patógeno hospitalar emergente, naturalmente resistente aos carbapenêmicos, que possui sulfametoxazol/trimetoprima (SMX-TMP) como opção terapêutica. Porém, relatos de resistência a essa droga começaram a aparecer. Objetivos: Avaliar o perfil de sensibilidade das cepas de S. maltophilia e comparar os resultados obtidos por diferentes metodologias. Método: As cepas isoladas na rotina microbiológica do Hospital das Clínicas de São Paulo em 2007 foram avaliad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
2
0
4
Order By: Relevance
“…The most prescribed carbapenem was meropenem, in 59 (72%) of the reports, as this carbapenem is the most used daily in hospitals, as its adverse reactions are milder than for imipenem and it is stable for long infusions, in addition to presenting greater efficacy against gram-negative bacilli, thus favoring its use Stenotrophomonas maltophilia is a bacterium considered naturally resistant to carbapenems, which justifies not carrying out the sensitivity test. As for Staphylococcus spp, during data collection it was observed that all the identified strains of this species were resistant to oxacillin, which leads us to consider them as carbapenem-resistant, as Methicillin-Resistant Staphylococcus aureus (MRSA) is resistant to all beta-lactams 20,28 .…”
Section: Rbfhssmentioning
confidence: 99%
“…The most prescribed carbapenem was meropenem, in 59 (72%) of the reports, as this carbapenem is the most used daily in hospitals, as its adverse reactions are milder than for imipenem and it is stable for long infusions, in addition to presenting greater efficacy against gram-negative bacilli, thus favoring its use Stenotrophomonas maltophilia is a bacterium considered naturally resistant to carbapenems, which justifies not carrying out the sensitivity test. As for Staphylococcus spp, during data collection it was observed that all the identified strains of this species were resistant to oxacillin, which leads us to consider them as carbapenem-resistant, as Methicillin-Resistant Staphylococcus aureus (MRSA) is resistant to all beta-lactams 20,28 .…”
Section: Rbfhssmentioning
confidence: 99%
“…Nesta investigação, Stenotrophomonas maltophilia, Acinetobacter e Pseudomonas aeruginosa foram os bacilos gram-negativos não fermentadores mais prevalentes entre os isolados de hemoculturas. Esse dado é preocupante, tendo-se em vista que infecções causadas por esses microrganismos são de difícil tratamento, devido à elevada resistência aos antimicrobianos 19,20 .…”
Section: Morganella Morganii (1)unclassified
“…As infecções por essa espécie em indivíduos imunocompetentes são consideras incomuns, mas durante os últimos anos S. maltophilia vem se destacando como um agente nosocomial emergente, causando altos índices de mortalidade em infecções hospitalares, principalmente em imunocomprometidos (Rodrigues;Di Gioia;Rossi, 2011).…”
Section: Introductionunclassified